INOVASI PENGOLAHAN HASIL PERTANIAN KAPULAGA MENJADI ES KRIM KAPULAGA - Putra, I.G.A.M.; Widarta, I.W.R.; Putri, N.W.C.W.S.; Savitri, A.A.A.; Miranda, S.A.; Permatasari, I.G.A.F. (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Manukaya Village is located in the Tampaksiring District, Gianyar Regency. The potential of this village has not been optimally developed, especially in the field of processing agricultural products. One of the agricultural products that can be utilized more optimally in Manukaya Village is cardamom (Amomum compactum Soland). Cardamom is one of the spice plants produced by Indonesia which is also an export commodity. The purpose of this community service is to educate the public by increasing the potential of cardamom in Manukaya Village, Tampaksiring District, Gianyar Regency into processed cardamom ice cream food products. This service method is lectures and direct training to the community in Manukaya Village which is held at Wantilan Tribhuwana, Tatag Banjar, Manukaya Village, Tampaksiring District, Gianyar Regency. The results achieved from this community service activity were that the Manukaya village community was able to process cardamom into cardamom ice cream which was named Manukaya's Cardice (Cardamom Ice). Keywords: cardamom, innovation, ice cream, manukaya, gianyar